2021
DOI: 10.18433/jpps31500
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between the Risk of Hypertensive Disorders of Pregnancy and Folic Acid: A Systematic Review and Meta-Analysis

Abstract: Purpose: Although folic acid (FA) supplementation has been shown to reduce general cardiovascular risks, its impact on hypertensive disorders of pregnancy (HDP) is unclear. We performed a systematic review and meta-analysis to clarify the association between FA and the risk of HDP (pre-eclampsia (PE) and gestational hypertension (GH)). Methods: PubMed, EmBase, and Cochrane Library were searched up to June 18, 2020, stratified by type of disease, initiation time of FA, form of FA and pre-conception Body Mass In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
4
0
3
Order By: Relevance
“…Third, the between-study heterogeneity was significant even though we had considered different definitions of preeclampsia, different methods of measurement, participants' fasting status, and various conditions for storage. However, it was also reflected in other similar meta-analysis covering the correlation between trace elements or vitamins and preeclampsia (84)(85)(86).…”
Section: Figurementioning
confidence: 82%
“…Third, the between-study heterogeneity was significant even though we had considered different definitions of preeclampsia, different methods of measurement, participants' fasting status, and various conditions for storage. However, it was also reflected in other similar meta-analysis covering the correlation between trace elements or vitamins and preeclampsia (84)(85)(86).…”
Section: Figurementioning
confidence: 82%
“…In a 2021 meta-analysis, 20 studies with 359 041 patients were identified including three RCTs and 17 cohort studies. Pooled estimates showed an RR of 0.83 (95% CI 0.74 to 0.93, p=0.0008) for association between low-dose folic acid and the risk of pre-eclampsia 154. Multivitamins/minerals were not assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Se considera que las concentraciones de homocisteína por encima de 10 μM son factores de riesgo para esta condición. Hasta la fecha se han descrito varios mecanismos diferentes por los que la homocisteína induce estrés oxidativo (Yu et al, 2021):…”
Section: Conocidaunclassified
“…Por otra parte, es responsable de la aparición de patologías que son mediadas por una angiopatía o vasculopatía a nivel placentario como son: el aborto espontáneo que puede ser causado por los efectos embriotóxicos directos de la homocisteína. y, desde otra perspectiva, por la lesión vascular en la decidua con alteración en las vellosidades coriales (Yu et al, 2021).…”
Section: Conocidaunclassified